THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE TWO STAY TWO STRAY (TSTS) WITH PAIKEM APPROACH IN LEARNING MATHEMATICS ON THE MATERIAL CIRCLE AT THE SECOND GRADE/CLASS VIII OF SMPN 1 MAKASSAR - Rizka Ridha Ruslan (Universitas Negeri Makassar, 2018)
This study aims to determine the effectiveness of the implementation of cooperative learning model two stay two stray (TSTS) with PAIKEM approach in mathematics learning in eighth grade material loop9 SMP Negeri 1 Makassar. This research is an experimental research. The study design used is Pre-Experimental Design, namely the One-group pretest posttest design.The study included all students of class VIII SMP Negeri 1 Makassar and the sample class VIII9 selected by clusterrandom sampling. Data were analyzed using descriptive statistical analysis and inferential statistical analysis. Class VIII9 were given treatment that implement cooperative learning model two stay two stray with PAIKEM approach. The data collection technique used is the test result of learning, observation sheets, and sheets questionnaire. The results showed that: 1) the results of the eighth grade students to learn mathematics9 SMP Negeri 1 Makassar after the implementation of cooperative learning model two stay two stray by more than 74.9 PAIKEM approach (KKM) are in thecategory medium with a mean of 76.15, an increase result of learning mathematics (the gain) class VIII9 SMP Negeri 1 Makassar significantly and at the high category, the results of students' mathematics learning in class VIII9 SMP Negeri 1 Makassar after being taught to use the implementation of cooperative learning model two stay two stray approach PAIKEM achieve mastery classical, which is only 87.2% (over 80%), the standard deviation of 8.84, 2) students in learning activities with the implementation of cooperative learning model two stay two stray with PAIKEM approachin the category is very active with an average score of 4,54; and 3) a student's response on learning with the implementation of cooperative learning model two stay two stray with PAIKEM approaches are in positive category. Based on the criteria of effectiveness, the general implementation of cooperative learning model two stay two stray with PAIKEM effective approach in mathematics learning material in class VIII Circle9 SMP Negeri 1 Makassar